(3OQGSI ebGQfIs - (3HTQi NGdO JQcj(B, (3Gdehdis ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2010)
(3GdebOeI(B-(3GdaUd GdJegjOj (B: (3eaghe GdeSGge hHjGf eQcRg GdbGfhf (B: (3GdeWdH GdChd (B: (3eaghe GdeSGge (B: (3GdeWdH GdKGfj (B: (3HjGf GdeQcR GdbGfhf ddeSGge(B-(3GdaUd GdChd (B: (3GdGdJRGeGJ GdeGdjI GdeaQhVI Ydi GdeSGgejf (B: (3GdeHMK GdChd (B: (3GdGdJRGe HhaGA bjeI GdCSge GdfbOjI (B: (3GdeWdH GdChd (B: (3JYQja GdSge GdfbOj hGdhaGA GdLRFj dbjeJg (B: (3GdeWdH GdKGfj (B: (3JSOjO GdGbSGW GdHGbjI ef bjeI GdSge (B: (3GdeHMK GdKGdK (B: (3LRGA GdENdGd HGdhaGA HGdGbSGW GdeSJMbI (B: (3GdeHMK GdKGfj (B: (3GdGdJRGeGJ GdeGdjI GdCNQi (B: (3GdeWdH GdChd (B: (3GdGdJRGe HOaY bjeI GdCSge GdYjfjI (B: (3GdeWdH GdKGfj (B: (3GdGdJRGe HJMed GdNSGQI(B-(3GdaUd GdKGdK (B: (3GdGdJRGeGJ GdEOGQjI GdeaQhVI Ydi GdeSGgejf (B: (3GdeHMK GdChd (B: (3GdGdJRGe HGdeMGaXI Ydi eUdMI GdTQcI hCSQGQgG (B: (3GdeWdH GdChd (B: (3GdeQcR GdbGfhfj dQFjS hCYVGA eLdS GdEOGQI (B: (3GdeWdH GdKGfj (B: (3GdGdJRGe HGdeMJaXI Ydi GdeYdheGJ GdSQjI ddTQcI (B: (3GdeHMK GdKGfj (B: (3GdJRGe GdeSGgejf HGdNVhY dbQGQGJ GdgjFI GdYGeI (B: (3GdeWdH GdChd (B: (3Gdeaghe GdbGfhfj dCbdjI GdeSGgejjf (B: (3GdeWdH GdKGfj (B: (3GdCSGS GdbGfhfj dNVhY eSGgej GdCbdjI dbQGQGJ GdCZdHjI (B: (3GdeWdH GdKGdK (B: (3VeGfGJ eSGgej GdCbdjI ai ehGLgI bQGQGJ GdCZdHjI(B-(3GdNGJeI(B.s
(3HHdjhZQGajG(B: (3U(B.151-162s
Keywords: (3GdCSges; (3GdTQcGJs; (3GdTQcGJ GdeSGgeIs